Empty Spain and Catholicism: A Study in the Serranía de Cuenca - Jaspe Nieto, Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Catholic Christianity is an inseparable part of the cultural identity of rural Spain. The traditions and habits of the peoples of the agrarian environment have a religious origin that manifests itself in various ways in the different orders of local social life. This ethnographic research studies the presence, role, relevance and meaning of the religious elements that currently exist in various forms and manifestations in a representative town of the so-called emptied Spain.